Unreadability is the Reader's Problem: The Book of Mormon's Critique of the Antebellum US Public Sphere**Independent scholar, email: Jonathan.sudholt@gmail.com. (2017) - Sudholt, Jonathan
Abstract : This article reads The Book of Mormon as an attack on the incoherence of American nationalism – as, specifically, a book about the inevitability of its own irrelevance. That is, its primary objection is that in order for Joseph Smith to get any attention at all within the unruly public sphere of Jacksonian America, he had to write a book that would get him the wrong kind of attention – attention as a religious fanatic rather than as a critic of the culture that creates religious fanatics. Joseph Smith believed there was something rotten at the heart of America, but, being an uneducated farm boy from western New York, he had no way to express his anger in a manner that would allow him to be taken seriously. He could only be an 'authority' with regard to religion, and religious authority, being ubiquitous, was no authority at all. Smith tracks the way the American public sphere forced its marginalized persons to criticize it from a disadvantageous position, and the way those critiques were turned to the establishment's advantage. For Joseph Smith, freedom of speech in America has always been a tool of the political elites to keep the poor from speaking effectively.